Estimated Import Demand Function for Pakistan: A Disaggregated Analysis - Marwat, Imran Ullah Khan (JISR management and social sciences & economics, 2015)
The theme of the study was to estimate the elasticity of aggregated and selected disaggregated import demand function with relative prices and income for Pakistan from 1982 to 2011 on annual data. The most effective estimation tool was used (Auto-regressive Distributed Lag ARDL) by employing the Bounds Test method and Error Correction Modeling (ECM) techniques. The Un-restricted Error Correction Model (UECM) ARDL to calculate the long run elasticity of import while the short term dynamics is estimated through restricted ECM. In this research, aggregated import demand and disaggregated import demand commodities groups were made. Petroleum, Chemical, Manufacturing Goods and Machinery and Transport Groups are response variables whereas Gross Domestic Product (GDP) and Relative Prices variables are treated as explanatory variables. The disaggregated analysis of above mentioned various commodities groups are conducted in order to identify the fundamental drivers of import demand and to design fiscal and economic policy accordingly. The results indicated that at aggregated level, import demand with respective relative prices is elastic whereas it is inelastic with income in the long run. At disaggregated level, import demand with relative prices of machinery and transport group is elastic only while it is inelastic with income level in all selected disaggregated imports demand in long run. Furthermore, all import demand models are statistically significant having expected association and are stable in long run. In sort run aggregate import demand, petroleum and chemical groups are statistically significant while manufacturing goods, machinery and transport groups are insignificant. Furthermore all alternate hypotheses were accepted.